Insertion of common mutations into the human β-globin locus using GET Recombination and an EcoRI endonuclease counterselection cassette - Duangporn Jamsai (2018)
A large number of mutations have been described in the human β-globin locus causing thalassemia or various hemoglobinopathies. However, only a very limited number of these mutations have been studied in animal model systems in the context of the human β-globin locus. We report here the use of the GET Recombination system with an EcoRI/KanRcounterselection cassette to facilitate the introduction of the HbE (codon 26, GAG→AAG mutation and the codon 41-42 (-TTCT) deletion, two mutations found in high frequency in South-East Asia, into the human β-globin locus. The counterselection cassette was first inserted into the target sequence in the β-globin gene, and then a PCR fragment carrying the required modification was used to replace it. Efficient counterselection depends upon the tight regulation of the highly toxic EcoRI endonuclease gene by expression of lacIq. Induction by IPTG during counterselection efficiently eliminates non-recombinant bacterial clones. The technique can be performed on any known gene sequence using current BAC technology, allowing identification and comparative functional analysis of key regulatory elements, and the development of accurate animal models for human genetic disorders. © 2002 Elsevier Science B.V. All rights reserved.